Gender, politics and development in Accra, Ghana - Agyei-Mensah, S.; Wrigley-Asante, C. (Ashgate Publishing LtdAlternative Development: Unravelling Marginalization, Voicing Change, 2016)
African towns and cities are in the midst of social and economic change, which has attracted scholarly attention from a diverse range of disciplines. Some of these studies have focused on particular cities, as seen in the works of Stewart (1999) on the changing urban morphology of Cairo in Egypt, Gaule (2005) on the changing spatial patterns of Johannesburg in South Africa, and Grant (2009) on the impact of globalization on Accra in Ghana. Simone (2004) has studied strategies deployed to control, shape and make sense of urban life in several African cities: Pikine, a suburb of Dakar in Senegal; Winterveld, a neighborhood on the edge of Pretoria in South Africa; Douala in Cameroon; as well as the strategies of Africans seeking work in Jeddah, Saudi Arabia.